2016
DOI: 10.1371/journal.pone.0155234
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Test Abnormalities in Depressed Patients Treated with Antidepressants: A Real-World Systematic Observational Study in Psychiatric Settings

Abstract: BackgroundConcerning the risk of antidepressant induced liver injury, it is not clear whether psychiatrists perform a liver function test (LFT) and whether an increase in aminotransferase levels should contraindicate antidepressant treatment.AimTo evaluate LFT availability, the prevalence of LFT abnormalities and the probable cause of an altered LFT in patients with a major depressive episode (MDE) requiring an antidepressant drug.MethodsWe studied LFT evaluation in a real world psychiatric setting, in a sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In fact, a study conducted by the French Competent Authority (ANSM) on a cohort of more than 3.8 million subjects has established there was no argument supporting an increased risk of serious hepatic impairment related to the initiation of agomelatine treatment (taken in accordance with the SmPC) compared with selective serotonin reuptake inhibitors [ 48 ]. As hepatic transaminase elevation is seen with most antidepressants, their monitoring during, and on discontinuation of, treatment could be seen in general health care for depressed patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study conducted by the French Competent Authority (ANSM) on a cohort of more than 3.8 million subjects has established there was no argument supporting an increased risk of serious hepatic impairment related to the initiation of agomelatine treatment (taken in accordance with the SmPC) compared with selective serotonin reuptake inhibitors [ 48 ]. As hepatic transaminase elevation is seen with most antidepressants, their monitoring during, and on discontinuation of, treatment could be seen in general health care for depressed patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As consequence, the monitoring of transaminases values required since 2012 with respect of contra indications are the most effective ways of minimising hepatic risk. In general health care, such measures are considered adapted to ensure an optimal follow‐up of depressed patients (Voican et al, 2016). A recent analysis in a cohort comprising 3.2 million new users of antidepressants has shown that, in routine clinical practice, agomelatine did not increase the risk of hospitalisation due to acute liver injury when compared to citalopram (Pladevall‐Vila et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In our study SGOT and SGPT were elevated in the control group of patients as compared to patient group. [18] …”
Section: Discussionmentioning
confidence: 99%